Instructional modules in developing five reading comprehension skills among second year vocational college students - Mendoza, Miguel Balboa (1978)
This paper presented five instructional modules in developing reading comprehension skills among second year vocational college students. It dealt specifically with the construction, field try-out and refinement of the modules.